2017
DOI: 10.1177/0333102417714477
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in primary headaches in 48 countries: A physician-survey based study

Abstract: Aim To investigate the relationship between primary headache types and accomplished or attempted suicide in countries from all world regions. Methods Data were obtained using a questionnaire about suicide due to headache in a face-to-face interview with 203 physicians with expertise in headaches. They came from 48 countries, and from all continents. Results Primary headaches cause one suicide per 1,000,000 population each year (1% of the suicide rate due to all causes). Cluster headache and migraines account f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…It is well known that CM is associated to psychiatric comorbidities, including anxiety and depression (32,33), which may play a signi cant role in the way one perceives pain, copes with it and maintains a normal lifestyle. Furthermore, evidence from other elds of research showed that adults with anxiety disorders reportedly experienced signi cantly more total life events, perceived them as being more stressful, and adapted to them less well than normal controls (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that CM is associated to psychiatric comorbidities, including anxiety and depression (32,33), which may play a signi cant role in the way one perceives pain, copes with it and maintains a normal lifestyle. Furthermore, evidence from other elds of research showed that adults with anxiety disorders reportedly experienced signi cantly more total life events, perceived them as being more stressful, and adapted to them less well than normal controls (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Both migraine and psychiatric disorders are prevalent and burdensome conditions challenging the health care systems worldwide [15]. These conditions show a large overlap [6, 7] and epidemiological studies suggest that patients with migraine – especially those with chronic migraine (CM) and migraine with aura – are at increased risk for major depression, anxiety, or suicidal behavior when compared to subjects without migraine (e.g., [810]). Besides, according to a recent large genome-wide association study, when compared to other neurological disorders, migraine showed a higher genetic correlation with psychiatric disorders suggesting common genetic bases or pathways [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cluster headache (CH) is a headache disorder widely regarded as one of the most painful human experiences (Burish et al 2020) with a high rate of suicidal thoughts and attempts (Ji Lee et al 2019;Rozen and Fishman 2012;Trejo-Gabriel-Galan et al 2018). The diagnosis of cluster headache is made by defining criteria: 1-8 headache attacks per day of one side of the face, with each attack lasting between 15 min and 3 h, associated with restlessness and/or cranial autonomic features, such as a bloodshot eye and nasal congestion on the same side as the pain (Headache Classification Committee of the International Headache Society (IHS) 2018).…”
Section: Introductionmentioning
confidence: 99%